LONG-TERM FOLLOW-UP OF SKELETALLY IMMATURE PATIENTS WITH THE PHYSEAL-SPARING COMBINED EXTRA-/INTRA-ARTICULAR ILIOTIBIAL BAND ACL RECONSTRUCTION: KINEMATIC AND KINETIC RESULTS. Issue 3 (31st March 2019) - Sugimoto, Dai; Whited, Amy; Brodeur, Jeffery; Liotta, Elizabeth S.; Williams, Kathy; Kocher, Mininder S.; Micheli, Lyle J.; Heyworth, Benton E.
Background: Anterior cruciate ligament (ACL) tears are among the most devastating orthopaedic injuries affecting young athletes, especially when they occur in children and adolescents. Growing interest in physeal-sparing techniques has prompted various investigations into the combined extra-articular/intra-articular modified-Macintosh ACL reconstruction with Iliotibial band autograph (ACLR-ITB), which is often used for younger skeletally immature patients with complete ACL ruptures. However, several aspects of the long-term function of knees undergoing this technique remain under-investigated. Therefore, the purpose of the current study was to determine two critical parameters of knee function—the vertical ground reaction force (VGRF) and vertical jump height - at various time intervals following the ACLR-ITB: 1-2 years, 2-5 years, 5-10 years, and >10 years post-surgically. Methods: The current investigation was conducted at a single pediatric tertiary care center using a cross-sectional, laboratory-controlled study design. Inclusion criteria were skeletally immature patients with ACL tears who underwent an ACLR-ITB procedure. Exclusion criteria were major knee injuries (requiring rehabilitation > 3 months) or subsequent surgery on the ipsilateral knee and/or any surgery on the contralateral knee. During data collection, 29 reflective markers were applied to participants who performed drop vertical jumps (DVJ) three consecutive times and vertical single-limb hops (one time, each limb). A three dimensional (3D) motion analysis system with force plates was used. Kinematic and kinetic data were collected at 240 Hz and 1080 Hz respectively, and synchronized in time. The sequence of which limb was tested first in the vertical single-limb hop test was randomized. The instance of initial contact was identified and the landing phase was defined as the first 500 ms after initial contact. Major outcome variables included VGRF and vertical jump height. The VGRF were normalized by mass (kg), and mean peak values of the landing phase were used for analysis. Vertical jump height was calculated through following equation: ½ g(t/2)2, where g=9.81 m/s2 and t=time in seconds in the air. Descriptive statistics were used to analyze basic demographic characteristics. Paired t-tests were employed to compare VGRF and vertical jump height between the two limbs by four groups (1-2 years, 2-5 years, 5-10 years, and >10 years) separately. Additionally, equivalence analysis using two one-sided paired t-tests was applied to further support comparison of the two limbs. Any difference in the outcome measures (VGRF and vertical jump height) at the 26 patient-level was further tested to examine equivalency between the two limbs using a margin of equivalence of 4 (a difference less than 4 was not considered clinically important). The a priori statistical significance was set as p=0.05. Results: The study population consisted of 40 subjects (1-2 years: N=9; 2-5 years: N=13; 5-10 years: N=10; >10 years: N=8), with demographic information presented at Table 1. Based on available data (26 of 40, 19 males and 7 females, 1-2 years: N=6, 2-5 years: N=9, 5-10 years: N=7, >10 years: N=4), paired t-tests showed no statistically significant differences in VGRF and vertical jump height between ACLR-ITB and non-ACLR limbs in DVJ (Table 2) and vertical single-limb hop (Table 3) in any of the follow-up time groups. The equivalence analysis identified that the main outcome measures for the ACLR-ITB limb were equivalent to those of the non-reconstructed limb at the 26 patient-level (DVJ: p=0.016, VSH: p<0.001, JH: p=0.01; Note: p<0.05 confirms equivalency that the measures for the two limbs are close enough so that reconstructed limb cannot be considered superior or inferior to the native limb). Conclusion/Significance: Based on VGRF and vertical jump height in DVJ and vertical single-limb hop maneuvers through kinematic and kinetic analyses, ACLR-ITB knee demonstrated equivalent or superior function to the contralateral uninjured limbs at 1-2 years, 2-5 years, 5-10 years, and >10 years following reconstruction. These data contribute broader scientific support for the ACLR-ITB procedure offering lasting functional benefits for skeletally immature athletes with complete ACL tears. Table 1. Demographics of participants (N=26) Number (%) Age (years) Height (cm) Weight (kg) BMI (kg/m 2 ) Duration from ACLR-ITB to Data Collection 1-2 years (N=6) 23.1% 13.4 ± 2.7 160.7 ±22.7 53.1 ± 12.4 20.8 ±5.2 2-5 years (N=9) 34.5% 15.1 ± 1.3 170.2 ±8.3 65.8 ± 13.9 22.6 ±3.7 5-10 years (N=7) 26.9% 13.0 ± 2.0 177.8 ± 16.1 75.7 ± 20.9 24.2 ±7.1 > 10 years (N=4) 15.4% 22.0 ±2.6 168.1 ± 10.4 65.9 ±6.2 23.3 ±1.3 Values are mean ± standard deviation. Table 2. Comparison of normalized peak VGRF during DVJ ACLR-ITB Limb Non-ACLR Limb P-values Peak VGRF (NKg) 1-2 years (N=6) 15.7 ± 5.6 15.8 ±4.1 0.964 2-5 years (N=9) 16.7 ± 4.2 14.4 ± 3.1 0.056 5-10 years (N=7) 20.5 ± 10.8 17.0 ± 6.6 0.188 >10 years (N=4) 13.7 ± 0.9 11.7 ± 1.1 0.054 Values are mean ± standard deviation. Table 3. Comparison of normalized peak VGRF and vertical jump height during vertical single-limb hop Peak VGRF (NKg) ACLR-ITB Limb Non-ACLR Limb P-values 1-2 years (N=6) 25.2 ± 2.9 25.5 ± 1.9 0.776 2-5 years (N=9) 25.7 ± 3.4 25.4 ± 3.8 0.719 5-10 years (N=7) 30.3 ± 8.6 30.8 ± 7.3 0.545 >10 years (N=4) 23.5 ± 3.0 25.1 ± 3.0 0.135 Vertical Jump Height (Cm) 1-2 years (N=6) 9.3 ± 5.8 7.4 ± 6.0 0.051 2-5 years (N-9) 8.5 ±4.2 12.5 ± 12.0 0.415 5-10 years (N-7) 10.4 ± 2.2 8.8 ±3.1 0.069 >10 years (N-4) 9.2 ± 5.5 8.3 ± 4.7 0.148 Values are mean ± standard deviation